Multicenter Comparison of PCR Assays for Detection of Human Herpesvirus 8 DNA in Semen - Pellett, Philip E. (American Society for Microbiology, 1999)
Reported prevalences of human herpesvirus 8 (HHV-8) (Kaposi’s sarcoma-associated herpesvirus) in semen have ranged widely. This is possibly due to differences in assay sensitivity, geographic or population-based differences in the true presence of the virus in semen, and PCR contamination. This study assessed interlaboratory sensitivity and reproducibility in the analysis of blinded experimental panels, each consisting of 48 specimens and being composed of semen specimens from different healthy artificial-insemination donors (n = 30) and human immunodeficiency virus (HIV)-infected patients (n = 7) plus positive (n = 4) and negative (n = 7) controls. The experimental panels analyzed in each laboratory were identical except for being independently coded. Of 10 experiments done in five laboratories, 5 experiments from three laboratories had evidence of PCR contamination; all instances of contamination were in the context of nested PCR procedures. In the experiments with no false-positive results, HHV-8 DNA was detected in three (8%) of the 37 semen specimens (two from artificial-insemination donors and one from an HIV-positive patient) but in only 3 (1.6%) of the 184 PCRs in which these specimens were analyzed. This suggests that HHV-8 DNA is present in semen at concentrations that can be too low to allow its consistent detection. This study emphasizes the importance of performing blinded, multi-institution experiments to provide a coherent basis for comparing results and to motivate standardization of methods.